2015
DOI: 10.7727/wimj.2014.069
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Trauma in Pediatric Patients- Experience from Small Center

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…6 Our study revealed that the school going children (average age 7.05±3.9) were more vulnerable to BSI thus affirming the findings of Djordjevic et al who found that the maximum number of patients with abdominal trauma were seen in age group of 6-10 years. 9 The mean grade of splenic injury was 2.5, close to the grades reported by other authors. 10,11 Nevertheless, the grades of the injuries depend upon the mode and severity of the impact that a patient receives.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6 Our study revealed that the school going children (average age 7.05±3.9) were more vulnerable to BSI thus affirming the findings of Djordjevic et al who found that the maximum number of patients with abdominal trauma were seen in age group of 6-10 years. 9 The mean grade of splenic injury was 2.5, close to the grades reported by other authors. 10,11 Nevertheless, the grades of the injuries depend upon the mode and severity of the impact that a patient receives.…”
Section: Discussionsupporting
confidence: 87%
“…8 The male to female ratio was 3.2:1 which is comparable to the observations made by other studies. 9 Male children are more likely to have traumatic injuries especially younger males with lack of parental supervision. 6 Our study revealed that the school going children (average age 7.05±3.9) were more vulnerable to BSI thus affirming the findings of Djordjevic et al who found that the maximum number of patients with abdominal trauma were seen in age group of 6-10 years.…”
Section: Discussionmentioning
confidence: 99%
“…These results were comparable with that in literature. 8,9 Out of 45 patients with abdominal injuries, multiple intraabdominal solid organ injuries were present in six patients (13.3%) and isolated organ injury was present in 39 patients (86.6%). Two of them had (5%) combination of liver and kidney injuries, four patients had combination of spleen and kidney injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Intraabdominal injuries occur as a result of blunt abdominal trauma (BAT) or penetrating trauma, being BAT the most common cause (85%) and penetrating trauma accounting for only a minority (15%). Abdominal trauma is the third cause of death in children over 1 year of age [1,2]. Intraabdominal injuries are present in 5-10% of all BATs [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Other causes are sport injuries, falls and child abuse. Sport injuries usually cause isolated organ injury [1,2].…”
Section: Introductionmentioning
confidence: 99%